Entrepreneurial intention amongst scientists and their transition to roles in research based startups - NALLUR, Krishna Kumar (Institutional Knowledge at Singapore Management University, 2020)
The involvement of scientist and their transition to Research based Startup’s (RBSU’s) has been identified as a key factor in their success. This study was undertaken to better understand this transition of the scientist into the RBSU. It followed a two-step process of interviewing 28 researchers, researcher - entrepreneurs and researcher - startup employees followed by a survey with 104 individuals with similar backgrounds in research, entrepreneurship and as startup employees. the survey sought to understand the effects of entrepreneurial training / internships, access to entrepreneurs (network) and the role of events on these individuals and the likelihood of their participation in a spin off. The study identified that researchers transition to a RBSU is influenced by their orientations, researchers were found to have an entrepreneurial, impact or career orientation. Entrepreneurially oriented researchers typically have a breadth of early experiences and exposure to entrepreneurial activities and are more likely create or join a RBSU, career oriented are inclined to stay in their career of choice as a scientist researcher , they seem to be negatively influenced in making their transition as they have increasing exposure to events and networking opportunities related to entrepreneurship, however they may be join an RBSU if a trusted team exists at the RBSU, impact oriented researchers see RBSU’s as a means of creating impact for their research, they constantly seek to gain more information on how to manage RBSU’s and exposure to events and networking opportunities related to entrepreneurship result in a positive impact towards the creation of an RBSU, as they seek to identify partners to collaborate, bringing complimentary skills to the creation of a RBSU’s.